The Impact of Financial Literacy, Self-Control, and Digital Payment Usage on Generation Z's Consumer Behavior in West Jakarta - Elaine, Angelica; Dharma, Evani Kurnia; Amelinda, Rita (Journal of International Conference Proceedings, 2025)
This research seeks to examine the impact of financial literacy, self-control, and digital payment usage on the consumer behavior of Generation Z in West Jakarta. As a generation raised in the digital age, Generation Z demonstrates spending habits that are shaped by technological developments, including the convenience offered by digital payment platforms. The study adopts a quantitative approach, utilizing surveys through questionnaires distributed to Generation Z individuals living in West Jakarta. Data analysis is carried out using Outer Model and Inner Model evaluations. The findings reveal that financial literacy negatively influences consumer behavior, indicating that individuals with higher financial literacy are less likely to engage in excessive spending. Similarly, self-control also shows a negative relationship with consumerism, suggesting that those with stronger self-regulation tend to make more thoughtful purchasing decisions. In contrast, digital payment usage has a positive effect on consumerism, implying that transaction convenience may lead to increased impulsive buying. These results highlight the importance of developing more effective financial education programs tailored for Generation Z